2018
DOI: 10.1002/cphc.201800042
|View full text |Cite
|
Sign up to set email alerts
|

On the Solvation Behavior of Graphene Oxide in Ethylene Glycol/Water Mixtures

Abstract: The self-association and solvation pattern of graphene oxide (GO) in water, ethylene glycol (EG), and their mixtures were analyzed by means of UV/Vis spectrophotometry. A careful analysis of the absorbance dependencies vs. the GO concentration shows that self-association of the GO sheets in EG occurs at higher concentration compared to that in water. It was established that depending on the mixed solvent composition, two different types of the GO solvates are formed. The results of quantum chemical calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…EDO and water can associate with GONFs via hydrogen-bond interactions occurring within the first GONF layer as previously mentioned. 37,38 Because our previous work demonstrates that hydrated networks are able to provide a super-low frictional forces even between dissimilar friction pairs, 47 it is reasonable that hydrated GONFs−EDO networks play an important in the reduction of liquid shear stress in this study. Therefore, the low friction in the liquid-contact region mainly stems from the relative low shear stress at the EDO−GONF interface and between hydrated GONF and EDO networks.…”
Section: ■ Materials and Methodsmentioning
confidence: 77%
See 3 more Smart Citations
“…EDO and water can associate with GONFs via hydrogen-bond interactions occurring within the first GONF layer as previously mentioned. 37,38 Because our previous work demonstrates that hydrated networks are able to provide a super-low frictional forces even between dissimilar friction pairs, 47 it is reasonable that hydrated GONFs−EDO networks play an important in the reduction of liquid shear stress in this study. Therefore, the low friction in the liquid-contact region mainly stems from the relative low shear stress at the EDO−GONF interface and between hydrated GONF and EDO networks.…”
Section: ■ Materials and Methodsmentioning
confidence: 77%
“…When compared against Figure c, it can be observed that the interlayer spacing of GONFs remains unchanged after the prior rubbing motion. However, thicknesses of adsorbed GONFs after rubbing were observed to be larger compared to those of original GONFs, thereby indicating that GONFs in EDO solution might gather to form a thicker, adsorbed layer on friction surfaces subjected to rubbing motion . This provides better protection to surfaces against direct contact.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations